MORPHOMETRIC CHARACTERISTICS OF THE STONE OCTOPUS (Octopus cyanea) LANDED ON BARRANG CADDI ISLAND MAKASSAR CITY - Yuliana Arjun; Mesalina Tri Hidayani; Faturahman Attahrir; Yuliana Putri (Jurnal Riset Diwa Bahari (JRDB), 2026)
The stones octopus (Octopus cyanea) fishery is a prime export commodity for Indonesia; however, high exploitation pressure in the absence of stringent regulations on Barrang Caddi Island threatens the sustainability of its wild stocks. This study aims to analyze the morphometric characteristics of O. cyanea landed on Barrang Caddi Island. Specimens were collected from the catches of traditional fishers from December 2025 to January 2026 across eight sampling sessions. Body length dimensions were measured using a measuring tape with an accuracy of 0.1 cm across four primary parameters: total length, mantle length, mantle width, and arm length. Data were evaluated through a comparative statistical approach using an Independent Samples t-test (α = 0.05) to analyze morphometric variations between sexes. The results indicated that the morphometric characteristics of the stone octopus are generally monomorphic (p > 0.05), with a total length range of 59.6–62.6 cm and a mantle length range of 10.4–10.5 cm. Significant variations between sexes were exclusively identified in arm length (p < 0.05), where females exhibited longer arms (53.0±9.3 cm) as a functional adaptation for egg protection (brooding behavior). The catch was dominated by the 10 cm mantle size class, which is heavily influenced by gear selectivity (pocong-pocong and bole-bole), the West Monsoon season, and high fishing pressure driven by the island’s geographical proximity to the mainland. This truncated size structure indicates an early warning of growth overfishing. Therefore, these morphometric data are highly critical as a scientific baseline to design site-specific fisheries management frameworks, such as establishing minimum legal size limits, in the Spermonde Archipelago